2011
DOI: 10.1002/14651858.cd007248.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Propofol for procedural sedation/anaesthesia in neonates

Abstract: No practice recommendation can be made based on the available evidence regarding the use of propofol in neonates. Further research is needed on the pharmacokinetics of propofol in neonates and once a relatively safe dose is identified, randomised controlled trials assessing the safety and efficacy of propofol are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…180 One study compared propofol to morphine, atropine and suxamethonium for intubation and found that propofol led to shorter intubation times, higher oxygen saturations, and less trauma than the combination regimen in neonates, but these effects were not significantly different 181,182 However, propofol should be used with caution in young infants because its clearance and potential for neurotoxicity are inversely related to neonatal and postmenstrual age. There is significant inter-individual variability in the pharmacokinetics of propofol in preterm neonates 183 and its use can lead to severe hypotension, with transient decreases in heart rate and oxygen saturations.…”
Section: Non-opioid Therapiesmentioning
confidence: 99%
“…180 One study compared propofol to morphine, atropine and suxamethonium for intubation and found that propofol led to shorter intubation times, higher oxygen saturations, and less trauma than the combination regimen in neonates, but these effects were not significantly different 181,182 However, propofol should be used with caution in young infants because its clearance and potential for neurotoxicity are inversely related to neonatal and postmenstrual age. There is significant inter-individual variability in the pharmacokinetics of propofol in preterm neonates 183 and its use can lead to severe hypotension, with transient decreases in heart rate and oxygen saturations.…”
Section: Non-opioid Therapiesmentioning
confidence: 99%
“…In many European neonatal intensive care units, propofol is currently used as a standard single agent for endotracheal intubation. The used dosages are currently extrapolated from knowledge available from older children and adults . These dosages might be wrong because it is very reasonable to assume that neonatal propofol metabolism, transporters and receptors are immature .…”
Section: Introductionmentioning
confidence: 99%
“…They reported faster intubation times, better oxygen saturation maintenance and shorter recovery times in the propofol group, and there was no difference in bradycardia or hypotension between the two groups. [5] A paucity of data remains regarding the use of propofol in infants; the Cochrane review by Shah et al [27] only included the 63 infants in Ghanta et al's RCT. There are also significant concerns regarding the safety of propofol, Welzing et al [28] demonstrating a significant drop in arterial blood pressure when propofol was injected as a fast push.…”
Section: Discussionmentioning
confidence: 99%